Enhanced oil recovery by using polymer flooding Kenyalang field Baram Delta province [electronic resource] - Siti Saodah Tajudin, 1988- (2011)
Project Paper (Sarjana Muda Kejuruteraan (Petroleum)) - Universiti Teknologi Malaysia, 2011